Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To find the required functions and their domains, we need to perform basic operations on the given functions [tex]\( f(x) = 3x - 8 \)[/tex] and [tex]\( g(x) = x - 3 \)[/tex].
### 1. Addition: [tex]\( (f + g)(x) \)[/tex]
First, add the functions:
[tex]\[ f(x) + g(x) = (3x - 8) + (x - 3) \][/tex]
Combine like terms:
[tex]\[ (3x + x) - (8 + 3) = 4x - 11 \][/tex]
Thus,
[tex]\[ (f + g)(x) = 4x - 11 \][/tex]
The domain of the sum [tex]\( (f + g)(x) \)[/tex] is all real numbers, denoted as [tex]\( \mathbb{R} \)[/tex], since the sum of two polynomials is a polynomial, and polynomials are defined for all real numbers.
### 2. Subtraction: [tex]\( (f - g)(x) \)[/tex]
Next, subtract the functions:
[tex]\[ f(x) - g(x) = (3x - 8) - (x - 3) \][/tex]
Distribute the minus sign and combine like terms:
[tex]\[ (3x - x) - (8 - 3) = 2x - 5 \][/tex]
Thus,
[tex]\[ (f - g)(x) = 2x - 5 \][/tex]
The domain of the difference [tex]\( (f - g)(x) \)[/tex] is also all real numbers, [tex]\( \mathbb{R} \)[/tex], since it is also a polynomial.
### 3. Multiplication: [tex]\( (fg)(x) \)[/tex]
Multiply the functions:
[tex]\[ f(x) \cdot g(x) = (3x - 8)(x - 3) \][/tex]
Distribute the terms:
[tex]\[ = 3x \cdot x - 3x \cdot 3 - 8 \cdot x + 8 \cdot 3 \][/tex]
[tex]\[ = 3x^2 - 9x - 8x + 24 \][/tex]
Combine like terms:
[tex]\[ = 3x^2 - 17x + 24 \][/tex]
Thus,
[tex]\[ (fg)(x) = (3x - 8)(x - 3) \][/tex]
The domain of the product [tex]\( (fg)(x) \)[/tex] is all real numbers, [tex]\( \mathbb{R} \)[/tex], since it is a polynomial.
### 4. Division: [tex]\( \left(\frac{f}{g}\right)(x) \)[/tex]
Finally, divide the functions:
[tex]\[ \left(\frac{f}{g}\right)(x) = \frac{3x - 8}{x - 3} \][/tex]
The expression [tex]\( \frac{f}{g} \)[/tex] takes all real numbers except where the denominator is zero. Set the denominator equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ x - 3 = 0 \][/tex]
[tex]\[ x = 3 \][/tex]
So, [tex]\( x = 3 \)[/tex] is not in the domain of [tex]\( \left(\frac{f}{g}\right)(x) \)[/tex]. Thus, the domain is all real numbers except [tex]\( x = 3 \)[/tex], denoted as:
[tex]\[ \mathbb{R} \setminus \{3\} \quad \text{or} \quad (-\infty, 3) \cup (3, \infty) \][/tex]
In summary:
[tex]\[ (f + g)(x) = 4x - 11 \quad \text{with domain} \quad \mathbb{R} \][/tex]
[tex]\[ (f - g)(x) = 2x - 5 \quad \text{with domain} \quad \mathbb{R} \][/tex]
[tex]\[ (fg)(x) = (3x - 8)(x - 3) \quad \text{with domain} \quad \mathbb{R} \][/tex]
[tex]\[ \left(\frac{f}{g}\right)(x) = \frac{3x - 8}{x - 3} \quad \text{with domain} \quad \mathbb{R} \setminus \{3\} \][/tex]
### 1. Addition: [tex]\( (f + g)(x) \)[/tex]
First, add the functions:
[tex]\[ f(x) + g(x) = (3x - 8) + (x - 3) \][/tex]
Combine like terms:
[tex]\[ (3x + x) - (8 + 3) = 4x - 11 \][/tex]
Thus,
[tex]\[ (f + g)(x) = 4x - 11 \][/tex]
The domain of the sum [tex]\( (f + g)(x) \)[/tex] is all real numbers, denoted as [tex]\( \mathbb{R} \)[/tex], since the sum of two polynomials is a polynomial, and polynomials are defined for all real numbers.
### 2. Subtraction: [tex]\( (f - g)(x) \)[/tex]
Next, subtract the functions:
[tex]\[ f(x) - g(x) = (3x - 8) - (x - 3) \][/tex]
Distribute the minus sign and combine like terms:
[tex]\[ (3x - x) - (8 - 3) = 2x - 5 \][/tex]
Thus,
[tex]\[ (f - g)(x) = 2x - 5 \][/tex]
The domain of the difference [tex]\( (f - g)(x) \)[/tex] is also all real numbers, [tex]\( \mathbb{R} \)[/tex], since it is also a polynomial.
### 3. Multiplication: [tex]\( (fg)(x) \)[/tex]
Multiply the functions:
[tex]\[ f(x) \cdot g(x) = (3x - 8)(x - 3) \][/tex]
Distribute the terms:
[tex]\[ = 3x \cdot x - 3x \cdot 3 - 8 \cdot x + 8 \cdot 3 \][/tex]
[tex]\[ = 3x^2 - 9x - 8x + 24 \][/tex]
Combine like terms:
[tex]\[ = 3x^2 - 17x + 24 \][/tex]
Thus,
[tex]\[ (fg)(x) = (3x - 8)(x - 3) \][/tex]
The domain of the product [tex]\( (fg)(x) \)[/tex] is all real numbers, [tex]\( \mathbb{R} \)[/tex], since it is a polynomial.
### 4. Division: [tex]\( \left(\frac{f}{g}\right)(x) \)[/tex]
Finally, divide the functions:
[tex]\[ \left(\frac{f}{g}\right)(x) = \frac{3x - 8}{x - 3} \][/tex]
The expression [tex]\( \frac{f}{g} \)[/tex] takes all real numbers except where the denominator is zero. Set the denominator equal to zero and solve for [tex]\( x \)[/tex]:
[tex]\[ x - 3 = 0 \][/tex]
[tex]\[ x = 3 \][/tex]
So, [tex]\( x = 3 \)[/tex] is not in the domain of [tex]\( \left(\frac{f}{g}\right)(x) \)[/tex]. Thus, the domain is all real numbers except [tex]\( x = 3 \)[/tex], denoted as:
[tex]\[ \mathbb{R} \setminus \{3\} \quad \text{or} \quad (-\infty, 3) \cup (3, \infty) \][/tex]
In summary:
[tex]\[ (f + g)(x) = 4x - 11 \quad \text{with domain} \quad \mathbb{R} \][/tex]
[tex]\[ (f - g)(x) = 2x - 5 \quad \text{with domain} \quad \mathbb{R} \][/tex]
[tex]\[ (fg)(x) = (3x - 8)(x - 3) \quad \text{with domain} \quad \mathbb{R} \][/tex]
[tex]\[ \left(\frac{f}{g}\right)(x) = \frac{3x - 8}{x - 3} \quad \text{with domain} \quad \mathbb{R} \setminus \{3\} \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.